(untitled) (BIS Humanities and Social Science, 2026)
This study explores that Cultural Ambassadors play a strategic role in introducing and promoting the cultural richness and tourism potential of Samarinda, the capital city of East Kalimantan, Indonesia. As representatives of the younger generation who understand local cultural values, they act as communicators, educators, and promoters in disseminating information about tourist destinations, traditions, arts, and local wisdom to the wider community, including domestic and international tourists. With strong cultural knowledge and good communication skills, Cultural Ambassadors help create a positive image of Samarinda as a city rich in cultural heritage and worth visiting. Through qualitative methods, including interviews, case studies, and document analysis, this research aims to determine the importance of the role of Cultural Ambassadors in carrying out their duties to promote tourism in Samarinda. The findings reveal that they play a central role in cultural preservation, tourism marketing, and community engagement, especially through social media platforms and public events. The study concludes with recommendations for strengthening ambassador training, cross-sector collaboration, and the use of digital media in promoting Samarinda as a culturally vibrant and sustainable tourist destination.